የቡና መመሪያ፡ አራተኛ እትም። - International Trade Centre (United Nations, 2024)
The Coffee Guide is the world’s most extensive, hands-on, and neutral source of information on the international coffee trade. It covers trade issues relevant to coffee growers, traders, exporters, transportation companies, certifiers, associations and authorities, and other relevant actors. Many in the coffee industry consider it the go-to reference. This fourth edition is directly informed by the coffee industry, and it has updated technical information on finance, food safety measures, logistics, and contracts. It has redefined quality and data segmentation and expanded digitalization coverage and information related to certifications and supply chain legislation. It also gives prime importance to issues like climate change, coffee price volatility, living wage, and the inequitable distribution of power, profit, and resources across the supply chain. It aims to be informative, useful, and inclusive of all sector stakeholders.